The Winner's Curse and Bidder Competition in Acquisitions: Evidence from Failed Bank Auctions - Giliberto, S. Michael; Varaiya, Nikhil P. (Journal of Finance, 1989)
This study examines the effect of bidder competition in acquisitions. We use predictions from auction theory to test whether acquirers of failed banks overpay (the “winner's curse”) when bidding in FDIC sealed-bid purchase and assumption (P&A) transactions (auctions). The empirical results indicate that winning bids tend to increase as the number of competitors increases, as predicted by theory. We also find that bid levels of all bidders increase with increased competition, which is consistent with bidders' failing to adjust for the winner's curse in a common value auction setting. However, additional tests using winning bids only are consistent with both a common value and a private values model, so this result should be interpreted with caution.